Soft tissue adhesive as well as preparation method and application thereof
By adopting a soft tissue adhesive design with a three -layer structure composite, the problem of not matching the adhesive in the existing technology in the reimbing process of the adhesive is not matched with the degradation rate and the repair cycle, and the efficient soft tissue repair and degradation effect are achieved.
Patent Information
- Application Number
- CN202411378122.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-28
AI Technical Summary
Existing medical soft tissue adhesives are prone to cause problems in which adhesion and degradation rates do not match the repair cycle during the repair process.
Soft tissue adhesive design with a three -layer structure composite, including the bonding layer, anti -adhesive layer and strength degradation regulatory layer. The bonding layer is used for wound closed, the anti -adhesive layer is used for isolation tissue, and the intensity degradation regulatory layer is based on the control intensity and degradation cycle according to the needs of the tissue needs.
It effectively solves the problem of adhesion and degradation rates that do not match the repair cycle during the reimbing of adhesives, improves the adhesive strength and tissue adhesion, and meets the softness and degradation needs of soft tissue.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the field of biomedical technology, and in particular to a soft tissue adhesive and a preparation method and application thereof. Background Art
[0002] Medical soft tissue adhesives have attracted much attention since their introduction. Currently, many types of medical soft tissue adhesives are on the market, mainly used in medical fields such as heart and blood vessel repair, lung repair, and soft tissue repair. Its advantages are mainly reflected in easy implementation, rapid application, reduced tissue damage, and compatibility with minimally invasive surgery. However, while it plays a therapeutic role, it also has certain adverse reactions. Therefore, further research and improvement of medical soft tissue adhesives has become a hot topic in current research.
[0003] The selection of soft tissue adhesives depends largely on the target tissue, and the characteristics of various tissues vary greatly. For example, tissues such as the heart and lungs need to undergo repeated deformation or pulsating pressure, and their adhesives must have good flexibility to adapt to these disturbances. In addition, surface chemical properties, local tissue microenvironment, pathological state of the tissue, etc. will affect the adhesion, degradation and biocompatibility of the adhesive. Therefore, even though there are many types of soft tissue adhesives available, there is still no product that meets clinical needs, and soft tissue trauma repair is still mainly based on sutures or staples. Bonding in the body still requires a lot of research.
[0004] At present, soft tissue adhesives are roughly divided into two categories according to their raw material sources and working principles: one is protein adhesives based on hydrogen bonding, mainly fibrin and mussel protein. This type of adhesive has good flexibility and is currently widely used in clinical applications. It mainly adheres to tissues through hydrogen bonding. However, due to its limited bonding strength, it is limited to blocking and anti-adhesion after tissue suturing. The second is adhesives based on chemical synthesis, mainly cyanoacrylate adhesives. Because it has active groups that can bond with tissues, it can form a high-intensity force to achieve the purpose of bonding. However, due to its high hardness after action, strong foreign body sensation, and non-degradability after bonding, it cannot meet the needs of soft tissue flexibility and degradation, and has been limited to surface applications. Summary of the invention
[0005] The purpose of the present invention is to provide a soft tissue adhesive and a preparation method and application thereof, which solves the problem of low soft tissue bonding and repairing ability of adhesives in the prior art.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is:
[0007] The first aspect of the present invention provides a soft tissue adhesive, comprising: an adhesive layer, an anti-adhesion layer, and at least one strength degradation regulating layer formed between the adhesive layer and the anti-adhesion layer, wherein the adhesive layer at least comprises component A of the general structural formula I
[0008]
[0009] wherein R1 is -CH3 or -H, R2 is N-methylpyrrolidone, -H, -CH3 or pyrrolidone, R3 is -COOH, -OH, carbonylethanol or amide, R4 is N-hydroxysuccinimide, N-hydroxysulfosuccinimide, N-hydroxy-3,3-cyclopentaneglutarimide or N-hydroxyphthalimide, n1 and n2 indicate positive integers ranging from 20 to 60, and n3 indicates a positive integer ranging from 0 to 30;
[0010] The anti-adhesion layer at least includes component B, and the component B is a film-forming polymer.
[0011] Furthermore, the component A is obtained by copolymerizing at least monomer A1, monomer A2 and monomer A3, wherein the molecular structure of the compound A1 satisfies the general formula II:
[0012]
[0013] The molecular structure of component B satisfies the general formula III:
[0014]
[0015] Wherein, R1 is -CH3 or -H, R2 is N-methylpyrrolidone, -H, -CH3 or pyrrolidone, and R3 is -COOH, -OH, carbonylethanol or amide;
[0016] The compound A3 is N-hydroxysuccinimide, N-hydroxysulfosuccinimide, N-hydroxy-3,3-cyclopentaneglutarimide or N-hydroxyphthalimide.
[0017] Furthermore, the molar ratio of the monomer A1, the monomer A2 and the monomer A3 is 2:1:1.
[0018] Furthermore, the film-forming polymer is polycaprolactone, polylactide-co-glycolide, gelatin or modified gelatin.
[0019] Furthermore, the molecular weight of the polycaprolactone is 2000-5000, the molecular weight of the polylactide-glycolide is 10000-120000, and the molecular weight of the gelatin is 50000-100000.
[0020] Furthermore, the strength degradation regulating layer is formed by alternately coating at least one layer of the adhesive layer and at least one layer of the anti-adhesion layer.
[0021] A second aspect of the present invention provides a method for preparing a soft tissue adhesive, comprising the following steps:
[0022] (1) dissolving compound A1 and compound A2 in a first solvent and heating them, and then adding a condensing agent for condensation;
[0023] (2) After the condensation is completed, compound A3 is added to step (1) at room temperature to react to obtain component A;
[0024] (3) dissolving the component A in step (2) in a second solvent, followed by coating to form an adhesive layer;
[0025] (4) dissolving a film-forming polymer in a third solvent and then coating the solvent to form an anti-adhesion layer;
[0026] (5) alternately coating the adhesive layer and the anti-adhesion layer to form a strength degradation regulating layer;
[0027] (6) placing the adhesive layer, the strength degradation regulating layer and the anti-adhesion layer on a PTFE plate in sequence, covering the plate with the PTFE plate, applying pressure and drying, thereby obtaining the soft tissue adhesive.
[0028] Furthermore, in step (1), in step (1), the condensing agent is EDC, DCC or DIC.
[0029] Furthermore, the heating temperature in step (1) is 80-110° C. and the reaction time is 18-36 hours.
[0030] Furthermore, the reaction time in step (2) is 48 to 72 hours.
[0031] Furthermore, in step (1), the first solvent is DMF, DMSO, THF or TL; the second solvent is a mixed solution of chloroform and methanol; and the third solvent is chloroform, dichloromethane or ethyl acetate.
[0032] The third aspect of the present invention provides a use of a soft tissue adhesive in a medical adhesive.
[0033] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:
[0034] The present invention solves the problem of adhesion and mismatch between degradation rate and repair cycle in the existing adhesive repair process by combining the three-layer structure of adhesive layer, anti-adhesion layer and strength degradation regulation layer. The adhesive layer is used for wound adhesion and sealing, and plays the role of closing the wound surface; the anti-adhesion layer is used to isolate the wound tissue to avoid tissue adhesion; the strength degradation regulation layer can be regulated according to the strength and degradation cycle requirements of the tissue to be repaired. DETAILED DESCRIPTION
[0035] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] Embodiment 1:
[0037] This embodiment provides a soft tissue adhesive and a preparation method thereof, comprising the following steps:
[0038] (1) Install the reactor neck clamp, silicone gasket, PTFE stirring rod, and four-mouth open reactor cover on the open reactor flask in sequence, and fix them with stainless steel clamps. Place the four-mouth reactor into the bottom of the intelligent digital display constant temperature oil bath pot, fix it, add 100g DMF, start the stirrer, and adjust the speed to 250rpm. Set the oil bath pot temperature to 110℃, turn on the heating, and add 5.46g acrylic acid and 3.54g N-vinylpyrrolidone after the temperature stabilizes;
[0039] After the temperature stabilizes, slowly add 2.40 g of EDC in DMF (containing 0.1% EDC) at a rate of 1 mg / min. After the addition is complete, keep the mixture warm for 24 hours.
[0040] After the reaction solution was cooled to room temperature, 4.36 g of N-hydroxysuccinimide was added and reacted at room temperature for 72 h. After the reaction was completed, the mixture was washed with 100 g of ether for 6 times and dried in a safety explosion-proof oven at 40° C. for 2 h to obtain a functional compound for the adhesive layer.
[0041] (2) 5 g of the functional compound of the adhesive layer was dissolved in 20 g of chloroform / methanol solution (mass ratio 4:1), stirred at 37° C. for 2 h, and coated on a coater after being completely dissolved to prepare an adhesive layer film with a thickness of about 0.02 mm;
[0042] (3) 5 g of poly(lactide-co-glycolide) (50:50) was dissolved in 20 g of chloroform, stirred at 37° C. for 2 h, and coated on a coating machine after complete dissolution to prepare an anti-adhesion layer film with a thickness of about 0.02 mm;
[0043] (4) 5 g of the adhesive layer functional compound prepared in step (1) and 5 g of poly(lactide-co-glycolide) (50:50) were dissolved in 40 g of chloroform / methanol solution (mass ratio 4:1), and after being completely dissolved, they were coated on a coating machine to prepare a strength degradation regulating layer film with a thickness of about 0.02 mm;
[0044] (5) The adhesive layer film, strength degradation regulating layer film and anti-adhesion layer film prepared above are placed on a PTFE plate in sequence, and then covered with a PTFE plate of the same size, and a force of 5 kg is applied simultaneously, and dried at 120° C. for 48 hours to obtain a soft tissue adhesive.
[0045] Embodiment 2:
[0046] This embodiment provides a soft tissue adhesive and a preparation method thereof. The only difference between this embodiment and embodiment 1 is that component C used in step (1) is N-hydroxysulfosuccinimide, and the feeding amount is 2.15 g. Finally, a soft tissue adhesive is also prepared.
[0047] Embodiment 3:
[0048] This embodiment provides a soft tissue adhesive and a preparation method thereof. The only difference between this embodiment and embodiment 1 is that the film-forming polymer selected in step (3) is polycaprolactone, and a soft tissue adhesive is finally prepared.
[0049] Embodiment 4:
[0050] This embodiment provides a soft tissue adhesive and a preparation method thereof. The only difference between this embodiment and embodiment 1 is that the film-forming polymer selected in step (3) is gelatin, and a soft tissue adhesive is finally prepared.
[0051] Embodiment 5:
[0052] This embodiment provides a soft tissue adhesive and a preparation method thereof, comprising the following steps:
[0053] (1) Install the reactor neck clamp, silicone gasket, PTFE stirring rod, and four-mouth open reactor cover on the open reactor flask in sequence, and fix them with stainless steel clamps. Place the four-mouth reactor into the bottom of the intelligent digital display constant temperature oil bath, add 100g DMSO, start the agitator, and adjust the speed to 250rpm. Set the oil bath temperature to 80℃, turn on the heating, and add 10g propylene and 17.99g acrylic acid after the temperature stabilizes;
[0054] After the temperature stabilizes, slowly add 2.40 g of EDC DMSO solution (containing 0.1% EDC) at a rate of 1 mg / min. After the addition is complete, keep the mixture warm for 24 hours.
[0055] After the reaction solution was cooled to room temperature, 14.36 g of N-hydroxysuccinimide was added and reacted at room temperature for 48 h. After the reaction was completed, the mixture was washed with 100 g of ether for 6 times and dried in a safety explosion-proof oven at 40° C. for 2 h to obtain a functional compound for the adhesive layer;
[0056] (2) 0.25 g of the functional compound of the adhesive layer was dissolved in 20 g of chloroform / methanol solution (mass ratio 4:1), stirred at 37° C. for 4 h, and coated on a coater after being completely dissolved to prepare an adhesive layer film with a thickness of about 0.01 mm;
[0057] (3) 0.25 g of poly(lactide-co-glycolide) (50:50) was dissolved in 20 g of chloroform, stirred at 37° C. for 2 h, and coated on a coating machine after being completely dissolved to prepare an anti-adhesion layer film with a thickness of about 0.01 mm;
[0058] (4) coating the prepared adhesive layer functional compound and the anti-adhesion layer alternately, coating the adhesive layer with 3 layers and the anti-adhesion layer with 2 layers, to prepare a film with a thickness of about 0.05 mm;
[0059] (5) The adhesive layer film, strength degradation regulating layer film and anti-adhesion layer film prepared above are placed on a PTFE plate in sequence, and then covered with a PTFE plate of the same size, and a force of 5 kg is applied simultaneously, and dried at 120° C. for 48 hours to obtain a soft tissue adhesive.
[0060] Embodiment 6:
[0061] This embodiment provides a soft tissue adhesive and a preparation method thereof, comprising the following steps:
[0062] (1) Install the reactor neck clamp, silicone gasket, PTFE stirring rod, and four-mouth open reactor cover on the open reactor flask in sequence, and fix them with stainless steel clamps. Place the four-mouth reactor into the bottom of the intelligent digital display constant temperature oil bath pot, fix it, add 100g DMSO, start the agitator, and adjust the speed to 250rpm. Set the oil bath pot temperature to 80℃, turn on the heating, and add 10g propylene and 17.99g acrylic acid after the temperature stabilizes;
[0063] After the temperature stabilizes, slowly add 3.20 g of EDC in DMF (containing 0.1% EDC) at a rate of 1 mg / min. After the addition is complete, keep the mixture warm for 24 hours.
[0064] After the reaction solution was cooled to room temperature, 14.36 g of N-hydroxyphthalimide was added and reacted at room temperature for 48 h. After the reaction was completed, the mixture was washed with 100 g of ether for 6 times and dried in a safety explosion-proof oven at 40° C. for 2 h to obtain a functional compound for the adhesive layer.
[0065] (2) 0.25 g of the functional compound of the adhesive layer was dissolved in 20 g of chloroform / methanol solution (mass ratio 4:1), stirred at 37° C. for 4 h, and coated on a coater after being completely dissolved to prepare an adhesive layer film with a thickness of about 0.01 mm;
[0066] (3) 0.25 g of polycaprolactone was dissolved in 20 g of chloroform, stirred at 37° C. for 2 h, and coated on a coating machine after complete dissolution to prepare an anti-adhesion layer film with a thickness of about 0.02 mm;
[0067] (4) coating the prepared adhesive layer functional compound and the anti-adhesion layer alternately, coating one adhesive layer and one anti-adhesion layer, to prepare a film with a thickness of about 0.03 mm;
[0068] (5) On the basis of the above film, two layers of anti-adhesion layer were continuously coated to prepare a film with a thickness of about 0.05 mm, which was then placed on a PTFE plate and then covered with a PTFE plate of the same size. A force of 5 kg was simultaneously applied and the film was dried at 120° C. for 48 h to obtain a soft tissue adhesive.
[0069] Embodiment 7:
[0070] This embodiment provides a soft tissue adhesive and a preparation method thereof, comprising the following steps:
[0071] (1) Install the reactor neck clamp, silicone gasket, PTFE stirring rod, and four-mouth open reactor cover on the open reactor flask in sequence, and fix them with stainless steel clamps. Place the four-mouth reactor into the bottom of the intelligent digital display constant temperature oil bath pot, fix it, add 100g DMSO, start the stirrer, and adjust the speed to 250rpm. Set the oil bath pot temperature to 80℃, turn on the heating, and add 14g N-methyl pyrrolidone and 9.47g acrylic acid after the temperature stabilizes. ;
[0072] After the temperature stabilizes, slowly add 2.40 g of EDC in DMF (containing 0.1% EDC) at a rate of 1 mg / min. After the addition is complete, keep the mixture warm for 24 hours.
[0073] After the reaction solution was cooled to room temperature, 8.36 g of N-hydroxypyrrolidone was added and reacted at room temperature for 48 h. After the reaction was completed, the mixture was washed with 100 g of ether for 6 times and dried in a safety explosion-proof oven at 40° C. for 2 h to obtain a functional compound for the adhesive layer;
[0074] (2) dissolving 0.25 g of the functional compound of the adhesive layer in 20 g of chloroform, stirring at 37° C. for 4 h, and coating on a coater after complete dissolution to prepare an adhesive layer film with a thickness of about 0.005 mm;
[0075] (3) 0.15 g of a polymer of polytrimethylene carbonate and polyurethane was dissolved in 20 g of chloroform, stirred at 37° C. for 2 h, and coated on a coating machine after being completely dissolved to prepare an anti-adhesion layer film with a thickness of about 0.005 mm;
[0076] (4) coating the prepared adhesive layer functional compound and the anti-adhesion layer alternately, coating two layers of the adhesive layer and one layer of the anti-adhesion layer, to prepare a film with a thickness of about 0.015 mm;
[0077] (5) On the basis of the above film, three layers of anti-adhesion layer were continuously coated to prepare a film with a thickness of about 0.03 mm, which was then placed on a PTFE plate and then covered with a PTFE plate of the same size. A force of 5 kg was simultaneously applied and the film was dried at 60° C. for 48 h to obtain a soft tissue adhesive.
[0078] Embodiment 8:
[0079] This embodiment provides a commercially available n-butyl cyanoacrylate.
[0080] Embodiment 9:
[0081] This embodiment provides a commercially available fibrin glue.
[0082] Embodiment 10:
[0083] This embodiment provides a commercially available mussel protein glue.
[0084] Embodiment 11
[0085] This embodiment provides a soft tissue adhesive and a preparation method thereof, which is different from Embodiment 1 only in that the amount of EDC is doubled, and finally a soft tissue adhesive is prepared.
[0086] Comparative Example 1
[0087] This embodiment provides a soft tissue adhesive and a preparation method thereof. The only difference between this embodiment and embodiment 1 is that component C is not added for reaction. Finally, a soft tissue adhesive is prepared.
[0088] The performance of the product prepared above is characterized as follows:
[0089] 1. Molecular weight and thickness characterization
[0090] Example No. Weight average molecular weight (adhesive layer) Film thickness / mm Example 1 29763 0.0313 Example 2 34987 0.0456 Example 3 32598 0.0424 Example 4 28347 0.0525 Example 5 28347 0.0512 Example 6 32598 0.0532 Example 7 45236 0.0312 Embodiment 11 84567 0.1143 Comparative Example 1 14437 0.0632
[0091] The adhesive layer in the present invention is prepared from olefins, propylene olefins and other materials, and the obtained polymer compound is a combination of carbon-carbon bonds and cannot be degraded. Therefore, the weight average molecular weight in the present invention is controlled below 50,000 and is excreted from the body through tissue absorption. After testing, except for Example 11, all others meet the requirements.
[0092] 2. Tensile strength
[0093] Take 5 finished products, cut the samples into strips with a width of 15mm and a length of 50mm, measure the thickness of three points within the sample gauge (evenly distributed) with a thickness gauge, and calculate the average thickness as the sample thickness. Put the sample vertically into the fixture of the electronic universal testing machine (using a 20N sensor), set the speed to 10mm / min, make the effective length 30mm, start the operation, and record the maximum load value and tensile strength when the sample breaks.
[0094]
[0095] Sample cross-sectional area (mm") = thickness 1m1, × width (m)
[0096] Example No. Tensile strength(Mpa) Example 1 46 Example 2 30 Example 3 45 Example 4 47 Example 5 36 Example 6 32 Example 7 40 Example 8 49 Example 9 1.2 Example 10 3.5 Embodiment 11 52 Comparative Example 1 12
[0097] Compared with other non-commercially available products, the tensile strength of Comparative Example 1 is lower because there is no group that reacts quickly with tissues in Comparative Example 1, and it mainly binds to tissues through intermolecular hydrogen bonds. Compared with the examples of non-commercially available products, the larger the molecular weight of the functional compound, the greater the tensile strength. However, it can be seen from the degradation data that the product hardly degrades after the molecular weight exceeds 50,000. Compared with commercially available products, each example has a bonding strength comparable to that of α-cyanoacrylate, which is much greater than commercially available protein adhesives.
[0098] 3. Bonding time
[0099] Take fresh animal liver, cut the membrane into 2*2cm squares (the commercially available product is applied to an area of 2*2cm), place the product on the surface of the animal liver, and record the curing time.
[0100] Example No. Curing time / s Example 1 19 Example 2 11 Example 3 19 Example 4 18 Example 5 32 Example 6 35 Example 7 39 Example 8 6 Example 9 / (No curing point) Example 10 / (No curing point) Embodiment 11 14 Comparative Example 1 20
[0101] The curing time of Examples 5, 6, and 7 is slightly slower than that of Examples 1-4 because the functional compounds of Examples 5, 6, and 7 have fewer active groups in the molecular structure than those of Examples 1-4, and the forces between the functional compounds and the tissues are slower to form. Compared with commercially available products, each of the Examples has a curing time comparable to that of α-cyanoacrylate, which does not exceed 1 minute, which is much shorter than commercially available protein adhesives.
[0102] 4. Shore hardness
[0103] The product simulates the clinical application of the product and is tested using a Shore A hardness tester. The specific test results are as follows:
[0104] Example No. Shore Hardness Example 1 23 Example 2 23 Example 3 25 Example 4 20 Example 5 90 Example 6 20 Example 7 20 Example 8 25 Example 9 23 Comparative Example 1 20
[0105] It can be seen from the above-mentioned Shore hardness test data that the Shore hardness of the adhesive prepared in the present invention is equivalent to that of fibrin and mussel protein glue. After the action, it is in a state similar to that of a gel and will not cause secondary damage to the tissue. The patient experience is strong.
[0106] 5. In vitro degradation study
[0107] According to the characteristics of the adhesive, Pbs buffer solution was used as an in vitro degradation reagent. Since this type of adhesive may degrade at high temperature, the degradation experiment was conducted under the extraction condition of 37°C. The conditions were 1w, 4w, 8w, 12w, and 26w respectively. The specific degradation experiments are as follows:
[0108]
[0109]
[0110] Through in vitro degradation studies, it can be seen that: from Comparative Example 1, the molecular weight of the adhesive layer is greater than 5W, and the product cannot be absorbed by the tissue; from Examples 1-7, it can be seen that the degradation rate of the anti-adhesion layer is the fastest for gelatin and the slowest for polycaprolactone. Considering that the cycle of complete repair of soft tissue is also 3-6 months, polylactide and polycaprolactone have a degradation cycle that matches tissue repair. At the same time, a suitable anti-adhesion layer can be selected according to different surgical sites. From Example 8, it can be seen that α-cyanoacrylate is not suitable for bonding soft tissues in vivo, and protein glue can only be used as a temporary closure and cannot play an effective bonding role.
[0111] 6. In vivo implantation / degradation studies
[0112] According to the results of the in vitro degradation experiment, the degradation cycles of the adhesives were comparable, so an in vivo implantation study was conducted using Example 1, with Example 8 used as a control. The implantation cycles of the in vivo degradation experiment were set to 1 month, 3 months, and 6 months, for a total of 3 experimental cycles.
[0113] (1) Degradation observation
[0114] Example Degradation 50% time Complete degradation absorption time Example 1 March June Example 8 No degradation observed No degradation observed
[0115] The repair period of lung injury is 3-6 months. The degradation period of the adhesive in the present invention is 3-6 months. After 6 months, the adhesive is no longer visible. Therefore, the adhesive has a degradation period that is compatible with tissue repair.
[0116] (2) HE section observation
[0117]
[0118] It can be seen from HE sections that the adhesive of the present invention has no obvious inflammatory reaction, the tissue has been completely repaired within 1 month, and a large number of inflammatory cells are still present around the tissue of Example 8 after 6 months, so the adhesive of the present invention has a good repair effect.
[0119] In summary, the soft tissue adhesive provided by the present invention has the characteristics of high bonding strength, good tissue adhesion and good flexibility, solves the problem of low bonding strength and poor wound closure strength of existing bioadhesives such as fibrin and mussel protein, and solves the problem of high hardness and strong foreign body sensation of cyanoacrylate adhesives.
[0120] As a composite membrane structure adhesive, it consists of a three-layer structure: an adhesive layer, an anti-adhesion layer, and a strength degradation regulation layer. The adhesive layer is used to bond and seal the wound, and plays a role in closing the wound surface; the anti-adhesion layer is used to isolate the traumatic tissue to avoid tissue adhesion; the strength degradation regulation layer can be regulated according to the strength and degradation cycle requirements of the tissue to be repaired. The three-layer structure design solves the problem that the existing adhesive repair process is prone to adhesion and the degradation rate does not match the repair cycle. At the same time, the innovative introduction of electron-rich active groups, through the principle of covalent bonding, better takes into account the effects of tissue adhesion and repair. It solves the problem that the existing adhesive has a single function, is only used for bonding, and does not have a repair function.
[0121] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the contents of the present invention and implement them accordingly. They cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A soft tissue adhesive, characterized in that: include: an adhesive layer, an anti-adhesion layer, and at least one strength degradation regulating layer formed between the adhesive layer and the anti-adhesion layer, The adhesive layer at least comprises component A of the general structural formula I Wherein, R1 is -CH3 or -H, R2 is N-methylpyrrolidone, -H, -CH3 or pyrrolidone, R3 is -COOH, -OH, carbonylethanol or amide, R4 is N-hydroxysuccinimide, N-hydroxysulfosuccinimide, N-hydroxy-3,3-cyclopentaneglutarimide or N-hydroxyphthalimide, n1 and n2 indicate positive integers ranging from 20 to 60, and n3 indicates a positive integer ranging from 0 to 30; The anti-adhesion layer at least includes component B, and the component B is a film-forming polymer.
2. A soft tissue adhesive according to claim 1, characterized in that: The component A is obtained by copolymerizing at least monomer A1, monomer A2 and monomer A3, wherein the molecular structure of the compound A1 satisfies the general formula II: The molecular structure of the compound A2 satisfies the general formula III: Wherein, R1 is -CH3 or -H, R2 is N-methylpyrrolidone, -H, -CH3 or pyrrolidone, and R3 is -COOH, -OH, carbonylethanol or amide; The compound A3 is N-hydroxysuccinimide, N-hydroxysulfosuccinimide, N-hydroxy-3,3-cyclopentaneglutarimide or N-hydroxyphthalimide.
3. A soft tissue adhesive according to claim 2, characterized in that: The molar ratio of the monomer A1, the monomer A2 and the monomer A3 is 2:1:
1.
4. The soft tissue adhesive according to claim 1, characterized in that: The film-forming polymer is polycaprolactone, polylactide-glycolide, gelatin or modified gelatin.
5. The soft tissue adhesive according to claim 3, characterized in that: The molecular weight of the polycaprolactone is 2000-5000, the molecular weight of the polylactide-glycolide is 10000-120000, and the molecular weight of the gelatin is 50000-100000.
6. The soft tissue adhesive according to claim 1, characterized in that: The strength degradation regulating layer is formed by alternately coating at least one layer of the adhesive layer and at least one layer of the anti-adhesion layer.
7. A method for preparing a soft tissue adhesive according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) dissolving compound A1 and compound A2 in a first solvent and heating them, and then adding a condensing agent for condensation; (2) After the condensation is completed, compound A3 is added to step (1) at room temperature to react to obtain component A; (3) dissolving the component A in step (2) in a second solvent, followed by coating to form an adhesive layer; (4) dissolving a film-forming polymer in a third solvent and then coating the solvent to form an anti-adhesion layer; (5) alternately coating the adhesive layer and the anti-adhesion layer to form a strength degradation regulating layer; (6) placing the adhesive layer, the strength degradation regulating layer and the anti-adhesion layer on a PTFE plate in sequence, covering the plate with the PTFE plate, applying pressure and drying, thereby obtaining the soft tissue adhesive.
8. The method for preparing a soft tissue adhesive according to claim 7, characterized in that: In step (1), the condensing agent is EDC, DCC or DIC; the heating temperature is 80-110° C., and the reaction time is 18-36 hours.
9. The method for preparing a soft tissue adhesive according to claim 7, characterized in that: In step (1), the reaction time in step (2) is 48 to 72 hours.
10. Use of the soft tissue adhesive according to any one of claims 1 to 6 in medical adhesives.